FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH BANK BCA CABANG KRANGGAN SEMARANG - Ninik Dwi Atmini; Jasman Indradno; Deddy Krisdiyanto (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of service quality, convenience, efficiency and trust on customer satisfaction of Bank BCA Kranggan Semarang Branch. The population in this study were customers of Bank BCA Kranggan Semarang Branch. Sampling in this study with non-probability sampling technique with purposive sampling type. Based on Slovin's calculation, there were 96 respondents. Data analysis using multiple linear regression test. The results showed that partially service quality, convenience, efficiency and trust in customer satisfaction. The value of the coefficient of determination on the effect of service quality, convenience, efficiency and trust on customer satisfaction of Bank BCA Kranggan Semarang Branch is 82%.